Neglected Musculoskeletal Trauma (Journal of Pakistan Orthopaedic Association, 2021)
Musculoskeletal injuries constitute a large proportion of global burden of trauma. Lack of proper treatment of musculoskeletal trauma results in disability and morbidity.1 In developing countries patients with musculoskeletal trauma usually do not present to hospital on time due to lack of transportation, poverty and ignorance. Furthermore many government hospitals do not have adequate infrastructure and trained staff resulting in delayed diagnosis or suboptimal treatment of these injuries. 2 Due to high influx of patients and constrained resources in state-owned hospitals of our country patients had to wait for their turn for surgery which cause frustration and anger amongst these patients and  most of them  leave hospital without definitive treatment and unfortunately do not get effective alternative treatment outside. Poverty and superstitious believes are a contributing factor for consulting bonesetters and improper treatment.3 Neglected musculoskeletal injuries are thus untreated injuries due to one or other reasons. In developed countries neglected musculoskeletal injuries are less frequent except missed injuries of the hip and spine reported in some polytrauma patients. Whereas in India  29% patients with fractures and dislocation in a teaching hospital had 50% neglected musculoskeletal injuries.4